2011
DOI: 10.1080/13572334.2011.545181
|View full text |Cite
|
Sign up to set email alerts
|

Microblogging, Constituency Service and Impression Management: UK MPs and the Use of Twitter

Abstract: Twitter, a microblogging site which allows users to deliver statements, thoughts and links in 140 characters to followers as well as a wider Internet audience, is the latest online communications technology adopted by MPs. Assessing the use of early adopters, this article considers which MPs are most likely to use Twitter (e.g. tweeting), and how. Content analysis of tweeting MPs was conducted, and identified personal and political characteristics which may influence use. The data suggested that of the six cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0
16

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(152 citation statements)
references
References 27 publications
3
118
0
16
Order By: Relevance
“…While our coding framework has developed independently over a number of years, this particular study was, to a certain extent, also influenced theoretically by work conducted by Jackson and Lilleker (2011), when they examined UK MPs' Twitter use. Jackson and Lilleker drew on two interrelated theories.…”
Section: Methodsmentioning
confidence: 99%
“…While our coding framework has developed independently over a number of years, this particular study was, to a certain extent, also influenced theoretically by work conducted by Jackson and Lilleker (2011), when they examined UK MPs' Twitter use. Jackson and Lilleker drew on two interrelated theories.…”
Section: Methodsmentioning
confidence: 99%
“…Legislative studies of this particular social media channel have, so far, largely focused on legislators' Twitter presence and activity around electoral campaigns (for extensive reviews, see Jungherr, 2014Jungherr, , 2016. Early studies found that legislators' party membership, age, gender, and seniority determine who uses Twitter and how often (Jackson & Lilleker, 2011;Lassen & Brown, 2011;Hemphill, Otterbacher, & Shapiro, 2013;Peterson, 2012). More recent research on the members of the European Parliament (MEPs), moreover, shows that voting systems, district magnitude, and seat safety are also important factors (Obholzer & Daniel, 2016;Scherpereel, Wohlgemuth, & Schmelzinger, 2016); presence and activity on Twitter increase with the incentives that these factors create for individual legislators to cultivate a personal vote.…”
Section: Case Selection Data and Methodsmentioning
confidence: 99%
“…More recent research on the members of the European Parliament (MEPs), moreover, shows that voting systems, district magnitude, and seat safety are also important factors (Obholzer & Daniel, 2016;Scherpereel, Wohlgemuth, & Schmelzinger, 2016); presence and activity on Twitter increase with the incentives that these factors create for individual legislators to cultivate a personal vote. With regard to the content, Twitter seems to mimic legislative communication practices in both form and substance, where legislators 'broadcast' their typical messages to voters in a way that leaves very little room for interactive communication (Golbeck, Grimes, & Rogers, 2010;Hemphill et al, 2013;Jackson & Lilleker, 2011;Saebø, 2011).…”
Section: Case Selection Data and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 2011 campaign, there was some evidence of the development of a Scottish version of what Jackson and Lilleker (2011) describe as a virtual "smoking room" -a Twitter community of politicians who communicate regularly with each other. Indeed, 3.6% of the overall candidate Twitter traffic was directed at other candidates; this compares with just a handful of posts exchanged between two candidates in 2010.…”
Section: De Gruytermentioning
confidence: 99%